The dual enrollment kaleidoscope: reconfiguring perceptions of first-year writing and composition studies - Denecker, Christine, editor; Moreland, Casie, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
The Dual Enrollment Kaleidoscope is a starting point for elevating the voices of those who historicize, legitimize, scrutinize, critically analyze, align, and assess dual enrollment (DE) work, pushing readers beyond singular views of DE first-year composition and positioning DE's impact on composition instruction as one that shifts dependent upon perspective.--Provided by publisher.
Introduction: the dual enrollment Kaleidoscope / Christine Denecker and Casie Moreland -- And yet the gap persists / Barbara Schneider, University of Toledo -- Dueling enrollments: historicizing the high school/college divide / Amy Lueck, Santa Clara University and Brice Nordquist, Syracuse University -- Location, delivery, and the historical divide between school and college English / Joseph Jones, University of Memphis -- The optics of observation: exploring tensions and opportunities at the high school-college composition threshold / Katie McWain and Jackie Hoermann-Elliott, with Jennifer Hadley, Texas Woman's University -- Navigating the landscape of professional development: dual enrollment teachers map college composition into the high school classroom / Melanie Burdick, Washburn University and Jane Greer, University of Missouri (Kansas City) -- High school teachers in the FYC ecology: revising the terms of contingency / Scott Campbell, University of Connecticut -- When college faculty go to high school: dual enrollment and the changing scenes of "First-Year" composition / Annie S. Mendenhall and David Gehler, Georgia Southern University (Armstrong) -- But it's (not) the same: a data-driven look at equivalency bias in dual enrollment composition / Dominic Ashby and Jill Parrott, Eastern Kentucky University -- Dislocating first-year composition: beyond the deficit model / Miles McCrimmon, Rappahannock Community College -- College composition at Midwest High: field notes from a concurrent enrollment classroom / Tyler Branson, University of Toledo -- Credit where credit is due: Willamette promise as an inclusive alternative to dual enrollment / Cornelia Paraskevas and Leigh Graziano, Western Oregon University -- Direct assessment of student learning in the eastern promise / Nancy Knowles, Eastern Oregon University -- Ready to write? A mixed methods study of dual enrollment composition students' writing self-efficacy and writing experiences / Erin D. Scott-Stewart, Southern University and A&M College -- Sidestepping the shame/blame binary: hearing and responding to dual enrollment students' voices in the composition classroom / Anna Bogen, The Ohio State University -- Afterword / Keith D. Miller and Shirley K Rose, Arizona State University.
Keywords: Dual enrollment -- United States; English language -- Rhetoric -- Study and teaching (Higher); English language -- Composition and exercises -- Study and teaching (Higher); Teachers -- Training of -- United States; High school students -- Education (Higher) -- United States; College credits -- United States